N, N′ N″-trisubstituted guanidines: Synthesis, characterization and evaluation of their leishmanicidal activity - do Espírito Santo, Rafael Dias [UNESP]; Velásquez, Ángela María Arenas [UNESP]; Passianoto, Luana Vitorino Gushiken [UNESP]; Sepulveda, Alex Arbey Lopera [UNESP]; da Costa Clementino, Leandro [UNESP]; Assis, Renata Pires [UNESP]; Baviera, Amanda Martins [UNESP]; Kalaba, Predrag; dos Santos, Fábio Neves; Éberlin, Marcos Nogueira; da Silva, Gil Valdo José; Zehl, Martin; et al. (Elsevier, 2019)
Leishmaniasis is a group of diseases caused by protozoan parasites from the genus Leishmania. There are estimated 1.3 million new cases annually with a mortality of 20,000–30,000 per year, when patients are left untreated. Current chemotherapeutic drugs available present high toxicity and low efficacy, the latter mainly due to the emergence of drug-resistant parasites, which makes discovery of novel, safe, and efficacious antileishmanial drugs mandatory. The present work reports the synthesis, characterization by ESI-MS, 1H and 13C NMR, and FTIR techniques as well as in vitro and in vivo evaluation of leishmanicidal activity of guanidines derivatives presenting lower toxicity. Among ten investigated compounds, all being guanidines containing a benzoyl, a benzyl, and a substituted phenyl moiety, LQOF-G2 (IC50-ama 5.6 μM; SI = 131.8) and LQOF-G7 (IC50-ama 7.1 μM; SI = 87.1) were the most active against L. amazonensis intracellular amastigote, showing low cytotoxicity to the host cells according to their selectivity index. The most promising compound, LQOF-G2, was further evaluated in an in vivo model and was able to decrease 60% of the parasite load in foot lesions at a dose of 0.25 mg/kg/day. Moreover, this guanidine derivative demonstrated reduced hepatotoxicity compared to other leishmanicidal compounds and did not show nephrotoxicity, as determined by the analyses of biomarkers of hepatic damage and renal function, which make this compound a potential new hit for therapy against leishmaniasis.
Keywords: Hepatoprotective effect; In vivo leishmanicidal activity; Leishmania amazonensis; Leishmaniasis; N, N′ N″-trisubstituted guanidine derivatives